Philips Lamp Product Innovation into UV-C Disinfectant Desk Lamp to Improve The Company's Competitiveness during The Covid-19 Pandemic - Ning Sunarno; Fajri Hamdani; Viana Anantasiska (Universitas Pendidikan Nasional, 2021)
The pandemic period is the reason for the company to set up an innovating strategy after conducting a series of research and product development. The purpose of Philips Company is to innovate not only to maintain the sustainability of product livecycle, but also to meet consumer needs for disinfectant tools by not leaving brand image in the pioneer of lighting products. Product innovation is done by designing products that effectively disable viruses, bacteria, fungi, and spores, in minutes. Consumer objectivity in deciding a product purchase due to the advantages of modern product design, energy saving, simple and put forward the ethics of environmentally friendly products.